Development of a multi-modality hydrogen delivery infrastructure: An optimization model for design and operation. (15th August 2022) - Parolin, Federico; Colbertaldo, Paolo; Campanari, Stefano
Graphical abstract: Highlights: A model for the optimal design and operation of a multi-modality hydrogen delivery infrastructure is developed. The modelled hydrogen supply chain comprises production, conditioning, storage, and transport up to demand nodes. The model optimizes the hydrogen delivery modality selecting between pipelines, gaseous trucks, and liquid trucks. The optimal infrastructure for long-term hydrogen mobility in Sicily reaches an average cost of hydrogen of 3.81 €/kg. The case study combines the three allowed transport modalities to exploit synergies. Abstract: Hydrogen deployment as an energy vector will play a crucial role in the decarbonization of the energy and industrial sectors. Its integration with the energy system requires the development of an adequate delivery infrastructure. The identification of an optimal design and operation strategy is complex due the variety of technological options in each stage of the hydrogen supply chain. This work develops a mixed-integer linear programming model to optimize the design and operation of a hydrogen infrastructure, comprising the entire supply chain from production to demand. A crucial novelty element is the combination of technical alternatives and modelling features. The proposed multi-modality formulation optimizes the transport technology at each stage, selecting between pipelines, compressed hydrogen trucks, and liquid hydrogen trucks. The pipeline and road networks are built through the model integration with a Geographic Information System, and the operation is tracked with a daily resolution, following the typical day approach. The model application looks at hydrogen employment for clean mobility in a long-term scenario in the Italian region of Sicily, assuming a demand of 1.1 million equivalent passenger cars (30% of today's stock). The resulting cost-optimal infrastructure features an average cost of delivered hydrogen of 3.81 €/kg, in line with mobility targets. The supply chain relies on the concurrent use of all transport modalities, thus showing that the multiplicity of options is a key asset in the development of a hydrogen economy.